Pulse wave velocity progression over a medium‐term follow‐up in hypertensives: Focus on uric acid. Issue 7 (21st June 2019) - Maloberti, Alessandro; Rebora, Paola; Andreano, Anita; Vallerio, Paola; De Chiara, Benedetta; Signorini, Stefano; Casati, Marco; Besana, Silvia; Bombelli, Michele; Grassi, Guido; Valsecchi, Maria Grazia; Giannattasio, Cristina
Abstract: The role of uric acid (UA) on the arterial stiffness progression has been evaluated only in three studies. Our aim was to evaluate its role as a possible determinant of the pulse wave velocity (PWV) progression over a 3.7 ± 0.5 years follow‐up period in hypertensive patients. Specific sex analysis was done due to the well‐known sex interaction with UA levels. We enrolled 422 consecutive hypertensive outpatients. At baseline anamnestic, blood pressure (BP) and laboratory data as well as PWV were assessed. PWV was performed again at follow‐up examination. Hyperuricemia was defined as a UA > 6 mg/dL for women and > 7 mg/dL for men. Baseline age was 53.2 ± 13 years, 58% were males, systolic and diastolic BP (SBP/DBP) 141.7 ± 17.7/86.8 ± 10.8 mm Hg, UA 5.2 ± 1.4 mg/dL, and PWV 8.5 ± 1.9 m/s. At follow‐up, despite better BP values (−8.5 ± 24.6 for SBP and −7.5 ± 15.4 for DBP), PWV increases to 9.1 ± 2.3 m/s ( P  < 0.001) with mean ΔPWV of+ 0.5 ± 2.2 m/s. A total of 61 patients were hyperuricemic (14.4%), and they present higher PWV baseline (9.0 ± 2.5 vs 8.5 ± 1.8 m/s, P  = 0.03) without significant differences in ΔPWV. Hyperuricemic female (6.2%, 11 patients) presents higher baseline PWV without significant differences in ΔPWV. No differences were found in arterial stiffness in hyperuricemic males (20.4%, 50 patients). UA showed association with baseline and ΔPWV in the whole population but it loses statistical significance at the linear regression model. Same figures were also for sex analysis. Our findings provide evidence that baseline UA levels are not determinants of PWV progression over a median follow‐up of 3.8 years' in hypertensive patients.